Faktor Risiko Keterlambatan Perkembangan Bicara dan Bahasa pada Anak Usia 24-48 Bulan - Desi Fitriani; Juniastuti; Ahmad Suryawan (STIKes MERCUBAKTIJAYA, 2022)
Speech and language skills are the determinants of all child development. Psychosocial factors are one of the most researched postnatal environmental factors, but most research only examines one of many psychosocial factors. In this research, 4 psychosocial factors will be researched. The purpose of this study was to determine the frequency of stimulation, quality of parent-child interaction, the intensity of the use of gadgets, and the duration of watching television as risk factors for speech and language delayed in children aged 24-48 months in Surabaya. This type of study was a case-control study in 122 children aged 24-48 months in 2 working areas of the Public Health Center in Surabaya. Data were analyzed by Chi-Square, contingency coefficient, and logistic regression test. The result showed that there was a relationship between the frequency of stimulation (p < 0.01), the quality of parent-child interaction (p < 0.01), the intensity of device use (p < 0.01), and television viewing duration (p < 0.01 ) with the risk of delayed speech and language development in children and the most dominant risk factor is the quality of parent-child interaction (OR 21,567). It can be concluded that frequency of stimulation, quality of parent-child interaction, the intensity of the use of gadgets, and duration of watching television are risk factors for delayed speech and language development in children aged 24-48 months, and the quality of parent-child interaction is the most influential risk factor. Keywords: speech and language development; children